If the sum of the coefficients of all


If the sum of the coefficients of all even powers of $x$ in the product

$\left(1+x+x^{2}+\ldots+x^{2 n}\right)\left(1-x+x^{2}-x^{3}+\ldots+x^{2 n}\right)$ is 61 , then $n$ is equal to___________.


Let $\left(1-x+x^{2} \ldots . . x^{2 n}\right)\left(1+x+x^{2} \ldots . . x^{2 n}\right)$

$=a_{0}+a_{1} x+a_{2} x^{2}+\ldots . .$

put $x=1$

$1(2 n+1)=a_{0}+a_{1}+a_{2}+\ldots . . a_{2 n}$.......(1)

put $x=-1$

$(2 n+1) \times 1=a_{0}-a_{1}+a_{2}+\ldots \ldots a_{2 n} \quad \ldots$ (2)

Adding (1) and (2), we get,

$4 n+2=2\left(a_{0}+a_{2}+\ldots \ldots\right)=2 \times 61$

$\Rightarrow 2 n+1=61 \Rightarrow n=30$

Leave a comment


Click here to get exam-ready with eSaral

For making your preparation journey smoother of JEE, NEET and Class 8 to 10, grab our app now.

Download Now